2007
DOI: 10.1017/s1751731107340068
|View full text |Cite
|
Sign up to set email alerts
|

Using n-alkanes to estimate diet composition of herbivores: a novel mathematical approach

Abstract: N-alkanes are long-chain saturated hydrocarbons occurring in plant cuticles that can be used as chemical markers for estimating the diet composition of herbivores. An important constraint of using n-alkanes to estimate diet composition with currently employed mathematical procedures is that the number of markers must be equal or larger than the number of diet components. This is a considerable limitation when dealing with free-ranging herbivores feeding on complex plant communities. We present a novel approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Apart from the different mathematical approaches (Dove 1992;Mayes et al 1994;Dove and Moore 1995;Martins et al 2002a;Barcia et al 2007) which can be used to overcome that limitation, other possible strategies include (i) to combine the discriminatory powers of the n-alkane method with other methods for estimating diet composition; (ii) to decrease the number of plant components to be discriminated by grouping species; (iii) to increase the number of markers in use (Mayes and Dove 2000). For example, microhistology has been used to identify the botanical composition of extrusa from oesophagical fistulated sheep feeding on grassland and shrublands (Salt et al 1994).…”
Section: Assessing Diet Composition and Voluntary Food Intake In Montadomentioning
confidence: 99%
“…Apart from the different mathematical approaches (Dove 1992;Mayes et al 1994;Dove and Moore 1995;Martins et al 2002a;Barcia et al 2007) which can be used to overcome that limitation, other possible strategies include (i) to combine the discriminatory powers of the n-alkane method with other methods for estimating diet composition; (ii) to decrease the number of plant components to be discriminated by grouping species; (iii) to increase the number of markers in use (Mayes and Dove 2000). For example, microhistology has been used to identify the botanical composition of extrusa from oesophagical fistulated sheep feeding on grassland and shrublands (Salt et al 1994).…”
Section: Assessing Diet Composition and Voluntary Food Intake In Montadomentioning
confidence: 99%
“…A number of mathematical algorithms and approaches including least squares optimisation procedures (Dove and Mayes, 2005) and linear programming (Barcia et al, 2007) have been developed and used for this purpose. Regarding the application of isotopic enrichment, Bugalho et al (2008) demonstrated that the linear programming model of Barcia et al (2007) can be effectively used to estimate the contribution of different sources to a mixture by relating the isotopic composition of carbon (d 13 C) and sulphur (d 34 S) in the sources and mixture. In relation to the present findings, it should also be possible to adopt a suitable mathematical model to use both the n-alkane profiles and their carbon isotopic compositions (d 13 C) as inputs in the calculation of diet compositions.…”
Section: Pc1mentioning
confidence: 99%
“…In more diverse swards there are usually more plant species available for consumption than there are alkanes to discriminate them. In this case different approaches can be taken: 1) decrease the number of dietary components by grouping species in the diet (e.g., grasses, legumes, and browse) or pooling species with similar n-alkanes profiles for statistical analyses; 2) combining the use of alkanes with other techniques such as microhistological examination of esophageal extrusa (Salt et al 1994) to estimate dietary components; 3) using other mathematical approaches in the use of n-alkanes as markers (Barcia et al 2007); or 4) using additional diet composition markers in plant wax: alkenes (unsaturated aliphatic hydrocarbons), long-chain alcohols (Bughalo et al 2004;Fraser et al 2006), and long chain fatty acids (Ali et al 2004(Ali et al , 2005. These components also have different concentrations in the different plant species and plant parts and can be obtained together with alkanes as part of the same analytical procedure (Dove and Mayes 2006).…”
Section: N-alkanes To Estimate Diet Compositionmentioning
confidence: 99%